Economic Transformation in the Era of Digitalization and Its Implications for the Employment Sector (Literature Review) - Wibowo, Arief Nugroho; Pangesti, Indah; Saputro, Firdaus Budhy; Dwi Cahyo, Ismail (PT Maju Malaqbi Makkarana, 2025)
The digitalization era has transformed the global economy and reshaped the labor market. This literature review examines the implications of digital transformation on economic structures and employment sectors. Key technologies, including artificial intelligence (AI), big data, and the Internet of Things (IoT), have accelerated business model evolution and enhanced efficiency across industries. However, these advancements have also disrupted traditional employment patterns by creating new job opportunities while simultaneously automating and eliminating manual labor roles. This study highlights the dual impact of digitalization: the emergence of flexible work through digital platforms and the risk of structural unemployment due to skill gaps and automation. Reskilling and upskilling are identified as essential strategies to prepare the workforce for evolving demands. Furthermore, governments and corporations must collaborate to develop adaptive employment policies and comprehensive training programs. While digitalization presents challenges, such as inequality and workforce displacement, it also offers opportunities for global connectivity, innovation, and economic inclusion. This paper concludes that leveraging these opportunities requires proactive strategies to ensure a dynamic and sustainable employment ecosystem.